Effect of a Yeast β-Glucan on the Performance, Intestinal Integrity, and Liver Function of Broiler Chickens Fed a Diet Naturally Contaminated with Fusarium Mycotoxins - Virginie Marquis; Julie Schulthess; Francesc Molist; Regiane R. Santos (Toxins)
This study evaluated the effect of a yeast β-glucan on the performance, gut health, liver function, and bacterial translocation of broiler chickens fed a diet contaminated with Fusarium mycotoxins. One-day-old male Ross broilers (n = 234) were divided into three treatments with six replicates each, and a cage containing 13 birds was the experimental unit. The animals were fed a maize–soybean-based control diet or maize–soybean diets naturally contaminated with Fusarium mycotoxins, where deoxynivalenol (DON) was the major mycotoxin (~3 mg/kg), followed by zearalenone (ZEN) (~0.5 mg/kg). The Fusarium-contaminated diet was either supplemented or not with a yeast β-glucan over 28 days. Dietary exposure to Fusarium mycotoxins did not affect production performance. On the other hand, Fusarium mycotoxin exposure significantly decreased jejunum villus height (VH) and crypt depth (CD) on d13, and this effect was counteracted by the yeast β-glucan. On d28, the jejunum VH:CD ratio was significantly higher in the broiler chickens that were fed the Fusarium-contaminated diet with yeast β-glucan (125 mg/kg diet) added to it. The ileal villus area was significantly decreased in the broiler chickens fed Fusarium-contaminated diet, regardless of the supplementation with yeast β-glucan. Dietary contamination caused intestinal oxidative stress and inflammation, probably affecting nutrient absorption on d28, and resulted in a significant increase in the translocation of Escherichia coli to the liver. Dietary supplementation with yeast β-glucan minimized these negative effects.